The Semantic Diversity of Characterizing Sentences - van Geenhoven, Veerle (Proceedings of the Amsterdam Colloquium, 2003)
Concentrating on the West Greenlandic aspect marker -tar-, I address the question of whether this kind of marker supports a uniform relational analysis of habitual and other characterizing sentences, as proposed in [12]. I argue that it does not. I show that the distribution of -tar-leads to a semantic diversity in the class of characterizing sentences, which brings along different sources of their nonparticular, generic nature.